2006
DOI: 10.1108/14717794200600024
|View full text |Cite
|
Sign up to set email alerts
|

Improving care transitions of older people: Challenges for today and tomorrow

Abstract: Enabling optimal care transitions for older people remains a key challenge facing policy‐makers and service providers. This qualitative Australian study aimed to provide a comprehensive picture of the factors/issues surrounding care transitions from the perspective of older people and their carers. It documents how supports and services are searched for and gained during the care transition process and the effect of this process on older people and their families. These findings have implications for service p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Manageable transitions exhibit features consistent with the goals of the GEM model of care (Ellis et al, 2011) and components of successful care transition interventions (Sahota et al, 2016). Numerous studies have reported the importance of active engagement of patients and the need to make adjustments to care plans based on patient experience (Coleman et al, 2004;Walker et al, 2015;Allen et al, 2016;Cheek et al, 2006) As reported elsewhere (Allen et al, 2016;Baillie et al, 2014;Giosa et al, 2014;Byrne et al, 2011) carers in this study had a critical role in optimising care transitions by seeking out information, negotiating with providers and promoting self-management. As reliance on carers can lead to them feeling overwhelmed by their role (Toscan et al, 2012) the expectations imposed by services and the work of carers in care transitions warrant further exploration.…”
Section: Discussionsupporting
confidence: 62%
“…Manageable transitions exhibit features consistent with the goals of the GEM model of care (Ellis et al, 2011) and components of successful care transition interventions (Sahota et al, 2016). Numerous studies have reported the importance of active engagement of patients and the need to make adjustments to care plans based on patient experience (Coleman et al, 2004;Walker et al, 2015;Allen et al, 2016;Cheek et al, 2006) As reported elsewhere (Allen et al, 2016;Baillie et al, 2014;Giosa et al, 2014;Byrne et al, 2011) carers in this study had a critical role in optimising care transitions by seeking out information, negotiating with providers and promoting self-management. As reliance on carers can lead to them feeling overwhelmed by their role (Toscan et al, 2012) the expectations imposed by services and the work of carers in care transitions warrant further exploration.…”
Section: Discussionsupporting
confidence: 62%
“…A central and recurring theme identified in this study is the difficulty experienced by carers in accessing and making sense of the information they were provided with about services ; a concern also acknowledged in the literature (Cheek et al 2006). In the case of respite services, the literature acknowledges the problem with carers' lack of awareness of the existence of respite and lack of knowledge about how to obtain it (Hanson, Tetley and Clarke 1999;Ritchie 2003 ;Witt, Chenoweth and Jeon 2004).…”
Section: Discussionmentioning
confidence: 82%
“…The impact of socio-economic factors on the likelihood of transition to nursing home care has also been examined, both in isolation and in conjunction with health conditions (Grundy and Jitlal 2007; Martikainen, Nihtilä and Moustgaard 2008; Miller and Weissert 2000). More broadly, the importance of care transitions by older people into community care as well as nursing homes is increasingly being recognised (Cheek et al 2006; Martikainen, Nihtilä and Moustgaard 2008; Mehdizadeh 2002).…”
Section: Introductionmentioning
confidence: 99%